Impact of HIV/AIDS on food and nutrition security: the case of Dire Dawa City administration, Ethiopia - Yizengaw, M.; Alemu, B.A.; Hanjra, Munir A. (2013)
This study examined the links between food security and HIV/AIDS in urban Ethiopia taking Dire Dawa city administration as a case example. The household level primary data were collected from selected kebeles - the lowest administrative unit in Ethiopia, - using a two stage sampling technique. In the first stage, four kebeles were selected due to their large number of known cases of people living with HIV (PLHIV). In the second stage, 200 households were randomly selected, taking 100 households each from HIV affected and non-affected category. Both quantitative and qualitative data were collected using well structured and pre-tested questionnaires, and key informant interviews and focus group discussions, which were held with the community members. Using weekly recall period, the data on food variety and quantity consumed were obtained from the principal person preparing food in the household, and then food consumption score was computed using the model developed by the World Food Program (poor consumption, borderline consumption, and better consumption with a score of <21, 21.5-35 and >35, respectively). Based on the results of the descriptive statistics, it was found out that food consumption score of HIV/AIDS affected and non-affected households were of 35.73 and 37.65, respectively suggesting that the latter are better off. About 70% of HIV affected households have food consumption score of less than 31.5 against 57% of the non-affected ones. Regression results of the ordered logit model also confirm this finding; holding all other variables constant, the marginal effect of being affected by HIV significantly increases the probability of the household being at poor and border line consumption category by 3.13% and 12.49%, respectively. On the other hand, being HIV affected decreases (by 15.62%) the probability of being in the better food consumption category. Thus HIV affected households were less likely to be food secure. Regression results further revealed that, ceteris paribus, participating in social networks significantly increased (by 20.01%) the probability of a household being in a better food consumption category. This suggests that socially isolated households may experience worse food insecurity situation because of lack of supportive safety nets that could shield them against shocks. Results further show that the coping strategies of HIV affected households include, among others, relying more on poor quality food, reducing the daily quantity of food intake and restricting the food consumption of adults in the family so that children can get a chance to eat. For households having fewer social networks and less diversified income sources, these stand out to be 'better' and affordable coping mechanisms. However, these coping strategies may hasten the death of HIV affected adult family members by weakening their health as they need more energy and proteins than non-affected ones. This was very well established during key informant interviews and focus group discussions. Therefore, future interventions should develop the capacity of both formal (legally established) and informal community based organizations to help avoid any forms of stigma or discrimination based on age, gender or sickness. Besides, it is vital to strengthen the human capital of HIV affected households and build resilient communities through better targeting and business skills development programs.